Lipoid proteinosisli iki olguda tekrarlayan oral ülserler - Dertlioglu, Selma Bakar; Cicek, Demet; Ozardalı, İlyas (Harran Üniversitesi, 2012)
Lipoid proteinozis LP nadir görülen otosomal resesif bir genodermatoz olup deri, oral kavite, larinks ve iç organlarda amorf hyalin kristal materyal birikimi ile karakterizedir. Birikim özellikle deride olmak üzere, üst solunum-sindirim sistemi mukozası ve iç organlarda olur. Hastalarımıza klinik bulgular, aile öyküsü ve histopatolojik değerlendirme sonucu LP tanısı konuldu. Hastaların dilinde tekrarlayan ağrılı ülserler mevcut olup nadir rastlanılan bu vakaları LP oral ülser birlikteliği açısından sunmayı uygun bulduk

Lipoid proteinosis LP is a rare autosomal recessive disorder characterized by infiltration of amorphous hyaline material in the skin, oral cavity, larynx, and internal organs. Deposition may be in different parts of the body, especially in the skin, mucous membranes of the upper aero digestive tract, and internal organs. LP was diagnosed with clinical findings, family history and histopathological evaluation. LP may be very rarely associated with oral ulcers. In this report, we aim to describe two cases of patients affected by LP associated with painful and recurrent ulcerative lesions in the tongue
Two cases of recurrent oral ulcers with lipoid proteinosis